Eletricidade no cotidiano para a EJA a partir dos três momentos pedagógicos - Silva, Cristian da Costa e (2019)
The present research study starts from the need to implement and analyze a didactic proposal that favors the scientific literacy of the students within the scope of the EJA. The promotion of literacy in this stage of schooling is important due to the fact that it favors the reconstruction of meanings about the world, starting from the historical and social baggage of these subjects, expanding knowledge, culture and the possibility of understanding and effectively participating in society. Based on these pre mises and accompanying the understanding that teaching science is linked to the search for answers to the problems of the students' daily life, the question that guides the investigation was formulated: To what extent did a didactic approach supported by the 3MP perspective favor student involvement of EJA with physical concepts? In order to respond to this questioning, we seek the support of the methodological proposal called Three Moments Pedagogical - 3MP, developed by Delizoicov and Angotti (1991) based on the work of Paulo Freire. From these choices it is formulated, as the objective of the study, to evaluate a didactic sequence to approach Physics contents in the EJA in terms of its contributions to the scientific literacy process. For the development of the research, a didactic sequence was structured addressing the theme “Electricity in everyday life”. This sequence is supported by 3MP and analyzes contributions to scientific literacy. The research developed was qualitative and participant, using the following instruments for data collection: teacher-researcher records in a logbook; audiovisual recording of classes; analysis of the material produced by the students during the application of the didactic sequence; analysis of the discussions carried out by students in the activity of knowledge systematization. The results discussed in these categories indicate that the didactic sequence was: favoring scientific literacy specifically in relation to the change in students' vocabulary, enriched with scientific terms and concepts; the identification of this knowledge in everyday situations; of the identification of the knowledge acquired through common sense; and on the role the importance of the theme and its conscious use for society. On the other hand, theelaborated didactic proposal was weakened when using technical mathematical calculations. The educational product accompanying the study refers to the elaborate didactic sequence and is made available in the form of teacher support material on the program site and the eduCapes Portal <http://educapes.capes.gov.br/handle/capes/553813>.